Epigenetic Modulation of Class-Switch DNA Recombination to IgA by miR-146a Through Downregulation of Smad2, Smad3 and Smad4 - Casali, Paolo; Li, Shili; Morales, Grecia; Daw, Cassidy C.; Chupp, Daniel P.; Fisher, Amanda D.; Zan, Hong (Frontiers in Immunology, 2021)
IgA is predominant antibody at mucosae. Dysregulation of IgA production can contribute to immunopathology, particularly in kidneys in which IgA deposition can cause nephropathy. Class-switch DNA recombination (CSR) to IgA is directed by TGF- signaling, which activates Smad2 and Smad3. Activated Smad2/Smad3 dimers are recruited together with Smad4 to the IgH  locus Iα promoter to activate germline Iα-Cα transcription, the first step in the unfolding of CSR to IgA. Epigenetic factors, such as non-coding RNAs, particularly microRNAs, have been shown to regulate T cells, dendritic cells and other immune elements, as well as modulate the antibody response, including CSR, in a B cell-intrinsic fashion. Here we showed that the most abundant miRNA in resting B cells, miR-146a, which targets Smad2, Smad3 and Smad4 mRNA 3’UTRs, keeps CSR to IgA in check in resting B cells. Indeed, enforced miR-146a expression in B cells aborted induction of IgA CSR by decreasing Smad levels. By contrast, upon induction of CSR to IgA, as directed by TGF-, B cells downregulated miR-146a, thereby reversing the silencing of Smad2, Smad3 and Smad4, which, once expressed, led to recruitment of Smad2, Smad3 and Smad4 to the Iα promoter for activation of germline Iα-Cα transcription. Deletion of miR-146a in miR-146a–/– mice significantly increased circulating levels of steady state total IgA, but not IgM, IgG or IgE, and heightened the specific IgA antibody response to OVA. In miR-146a–/– mice, the elevated systemic IgA levels were associated with increased IgA+ B cells in intestinal mucosae, increased amounts of fecal free and bacteria-bound IgA as well as kidney IgA deposition, a hallmark of IgA nephropathy. Increased germline Iα-Cα transcription and CSR to IgA in miR-146a –/– B cells in vitro proved that miR-146a-induced Smad2, Smad3 and Smad4 repression is B cell intrinsic. The B cell-intrinsic role of miR-146a in the modulation of CSR to IgA was formally confirmed in vivo by construction and OVA immunization of mixed bone marrow MT/miR-146a–/– chimeric mice. Thus, by inhibiting Smad2, Smad3 and Smad4 expression, miR-146a plays an important and B cell intrinsic role in modulation of CSR to IgA and the IgA antibody response.